Exploring the non-linear relationship and mechanisms linking green finance to tourism development - Cong, Shufeng; Chin, Lee; Xu, Lei (Routledge, 2024)
This study examines the impact of green finance on China’s tourism industry using panel data of 240 cities—both tourist and non-tourist—from 2011 to 2019. Our findings reveal an ‘inverted U’ relationship between green finance and tourism development in both tourist and non-tourist cities. We identified the threshold of green finance in tourist cities to be 0.302, higher than the threshold of 0.284 in non-tourist cities. In addition, international trade, foreign direct investment, and disposable income per capita were found to promote tourism, while urban price levels, integration of the digital economy, and air pollution showed an inhibitory effect on tourism development. The results also indicated that fixed asset investment is a promoting mechanism, while city loans, government expenditures, and tertiary industry serve as inhibiting mechanisms linking green finance to tourism. Overall, cities with lower levels of tourism development may need greater short-term financial support to facilitate their progress.